2018
DOI: 10.1002/gj.3220
|View full text |Cite
|
Sign up to set email alerts
|

Egyptian Hammamat molasse basins and their relations to arc collision stages: Implications for radioactive elements mineralization potential

Abstract: Our understanding of the formation style and tectonic setting of Hammamat molasse sedimentary rocks (HMSR) as well as their chronological situation in the legend of the geologic maps is as yet deficient. The purpose of the work is to decipher the misinterpretation of the HMSR genesis. As such, we present a new classification for HMSR that provides answers about its significant field relationships with the mature island arc volcanics that obviously explains the changes in the depositional environments of HMSR, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 55 publications
(106 reference statements)
0
2
0
Order By: Relevance
“…Hammamat sediments are widely distributed and cropped out in several localities forming large isolated exposures. Fowler and Osman (2013) and Dessouky et al (2019) mentioned that the Hammamat sediments are regionally folded into a major syncline forming a narrow elongated basin trending NW-SE. In the southern part of the basin, minor syncline-anticline folds are observed.…”
Section: Study Area and Geological Settingmentioning
confidence: 99%
“…Hammamat sediments are widely distributed and cropped out in several localities forming large isolated exposures. Fowler and Osman (2013) and Dessouky et al (2019) mentioned that the Hammamat sediments are regionally folded into a major syncline forming a narrow elongated basin trending NW-SE. In the southern part of the basin, minor syncline-anticline folds are observed.…”
Section: Study Area and Geological Settingmentioning
confidence: 99%
“…The Hammamat molasse of the ENS were developed between 650 and 580 Ma in individual basins in a variety of tectonic settings (Fritz and Messner, 1996;Shalaby et al, 2006;. Dessouky et al (2019) indicated that the Hammamat molasse sediments have been deposited during three tectonic settings: (i) precollision stage, comprising fore-arc, intra-arc and back-arc basins, (ii) syn-collision stage including fore-arc basins and lowland basins and (iii) late collision stage embracing lowland and intramontane basins.…”
Section: Dokhan Volcanics (620-550 Ma) and Hammamat Molasse Sediments (600-585 Ma)mentioning
confidence: 99%